Estrogen and Xenoestrogens in Breast Cancer - Fernandez, S.V. (2009)
There is growing concern that estrogenic environmental compounds that act as endocrine disrupting chemicals might potentially have adverse effects on hormone-sensitive organs such as the breast. This concern is further fueled by evidence indicating that natural estrogens, specifically 17 β-estradiol (E2), are important factors in the initiation and progression of breast cancer. We have developed an in vitro- in vivo model in which we have demonstrated the carcinogenicity of E2 in the human breast epithelial cells MCF-10F. Hypermethylation of NRG1, STXBP6, BMP6, CSS3, SPRY1 and SNIP were found at different progression stages in this model. The utilization of this powerful and unique model has provided a tool for exploring whether bisphenol A (BPA) and butyl benzyl phthalate (BBP) have relevance in the initiation of breast cancer. These studies provide first hand evidence that the natural estrogen 17 β-estradiol and xenoestrogenic substances like BPA are able to induce neoplastic transformation in human breast epithelial cells.